2018
DOI: 10.1016/j.jare.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant properties of curcumin derivatives by genetic function algorithm

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 34 publications
5
28
0
2
Order By: Relevance
“…However, these alterations were ameliorated by treatment with curcumin irrespective of the dose given. These findings were in agreement with the previous studies that have reported the antioxidant properties of curcumin [41][42][43].…”
Section: Discussionsupporting
confidence: 94%
“…However, these alterations were ameliorated by treatment with curcumin irrespective of the dose given. These findings were in agreement with the previous studies that have reported the antioxidant properties of curcumin [41][42][43].…”
Section: Discussionsupporting
confidence: 94%
“…However, Amalraj et al [20,21,25] concluded that CL caused a decrease in lipid peroxidation and an increase in antioxidant defense system activity in the CCl 4 -treated rats. Our findings are in accordance with previous reports of other related studies [17,18,23] that have suggested the protective role of CL powder, possibly due to the antioxidative effect of polyphenols and flavonoids present in the roots, that act as strong superoxide radicals and singlet oxygen quenchers. Also, we agree with Shakeri et al [26] who concluded treatment with CL rhizome extract caused an elevation of GSH levels, which protects the membranes against oxidative damage through regulation of the redox status of protein in the membrane.…”
Section: Discussionsupporting
confidence: 94%
“…e inhibition of lipid peroxides as well as an increase in SOD and G-Px activity, among the treatment groups (Txs) immediately after oral administration of CL (which peaked after three days) in the current investigation, could presumably be explained as protective effects of CL against oxidative damage. Furthermore, a decrease observed in MDA levels in the Tx groups following CL supplementation is suggestive that CL has appreciable free-radical scavenger properties and possesses the ability to suppress lipid peroxidation as similarly reported in previous studies [17]. Regulation of lipid peroxidation, radical scavenging, and antioxidant status may be one of the important mechanisms by which CL exerts its toxic inhibitory effect.…”
Section: Discussionsupporting
confidence: 84%
“…However, these alterations were ameliorated by treatment with curcumin irrespective of the dose given. These findings were in agreement with the previous studies that have reported the antioxidant properties of curcumin [47][48][49].…”
Section: Discussionsupporting
confidence: 94%